Diet quality and predictor factors of body weight status among children with learning disabilities in Kelantan - Mohamed, Siti Fathiah (2022)
Evidence suggests that children with Learning Disabilities (LD) have unhealthy Body Weight Status (BWS) and poor dietary patterns. A cross-sectional study was conducted to determine the diet quality and the predictors of Body Mass Index (BMI) of LD children. This study recruited LD children who attended the Special Education Integration Program from nine schools located in districts with high, moderate and low socio-economic status in Kelantan. Parents completed a Malay language self-administered questionnaire on demographic and socio-economic background, child’s feeding problems, food frequency questionnaire and comprehensive parental feeding practices. Height and weight of children were measured by researcher to determine BWS. Diet quality was assessed using The Malaysian Healthy Eating Index. Multiple linear regression analysis was applied to test the research hypothesis. A total of 259 children with LD aged 10.54±1.69 years (68.0% males, 32.0% females) participated in this study. Their average BMI was 18.38±4.79 kg/m2; males (18.79±4.76 kg/m2) had significantly higher BMI than females (17.52±4.77 kg/m2), p= 0.046. The prevalence of underweight, thin and severely thin were 11.9%, while 28.1% were overweight and obese. The diet quality average score was 48.15±9.23%, where 40.5% of the children were at risk of poor diet quality. The total daily energy intake was 1831.96±542.15 kcal with a mean carbohydrate intake (241.80±74.75g), protein intake (76.10±25.54g) and fat intake (63.42±21.33g), respectively. Majority of children had a higher score for the occurrence of rapid eating (2.00±1.32), food refusal (1.47±1.35), and food selectivity (1.26±1.13) during mealtimes in the past six months. Parental feeding practice including pressure to eat (Beta =-0.282), restriction of weight control (Beta =0.351) and modelling (Beta =-0.162), child age (Beta =0.222), and childbirth weight (Beta =0.137) were significantly related to BMI (R=0.561, R2=0.315; F(5,217) =19.972, p<0.001). The current findings suggested that early detection of nutrition issues in children with LD and regular positive feeding practice by parents during mealtime is essential to address the poor nutritional status of LD children.